2015
DOI: 10.1007/s11029-015-9504-9
|View full text |Cite
|
Sign up to set email alerts
|

Finite-Element Modeling of a Damaged Pipeline Repaired Using the Wrap of a Composite Material

Abstract: The nonlinear static problem of FEM modeling of a damaged pipeline repaired by a composite material and subjected to internal pressure is considered. The calculation is carried out using plasticity theory for the pipeline material and considering the polymeric filler and the composite wrap. The level of stresses in various zones of the structure is analyzed. The most widespread alloy used for oil pipelines is selected as pipe material. The contribution of each component of the pipeline-filler-wrap system to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…The stress-strain states in the corroded pipe area under the operational (internal) pressure, before and after repair, should be investigated and compared, together with the maximum stress/strain value in the pipe wall. Such investigations can be performed experimentally (results of pressure tests-some performed with the contribution of the authors-can be found in [28,30,31]), numerically (using finite elements simulation models-shown in [23,32,33]) or analytically.…”
Section: Reinforcement Effect Evaluation and Design Of The Composite Materials Repair Systemsmentioning
confidence: 99%
“…The stress-strain states in the corroded pipe area under the operational (internal) pressure, before and after repair, should be investigated and compared, together with the maximum stress/strain value in the pipe wall. Such investigations can be performed experimentally (results of pressure tests-some performed with the contribution of the authors-can be found in [28,30,31]), numerically (using finite elements simulation models-shown in [23,32,33]) or analytically.…”
Section: Reinforcement Effect Evaluation and Design Of The Composite Materials Repair Systemsmentioning
confidence: 99%
“…Окремі аспекти ремонту конструкцій з полімерно-композиційних матеріалів (ПКМ), у тому числі СО об'єктів обертання, наведено у [4][5][6]. Найбільш широко питання визначення напруженого стану та ремонту зазначених об'єктів шляхом накладення бандажів з ПКМ описані у [7][8][9][10][11][12].…”
Section: характеристика нс балону з соunclassified
“…is used, a small amount of the above expression can be neglected, and the simplified bending stiffness of the sandwich beam structure can be obtained. Then there is a bending stiffness ratio between the sandwich beam and the solid beam [6]:…”
Section: Composite Sandwich Theorymentioning
confidence: 99%